5(2n+3)=6(9n+8)+2

Simple and best practice solution for 5(2n+3)=6(9n+8)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2n+3)=6(9n+8)+2 equation:



5(2n+3)=6(9n+8)+2
We move all terms to the left:
5(2n+3)-(6(9n+8)+2)=0
We multiply parentheses
10n-(6(9n+8)+2)+15=0
We calculate terms in parentheses: -(6(9n+8)+2), so:
6(9n+8)+2
We multiply parentheses
54n+48+2
We add all the numbers together, and all the variables
54n+50
Back to the equation:
-(54n+50)
We get rid of parentheses
10n-54n-50+15=0
We add all the numbers together, and all the variables
-44n-35=0
We move all terms containing n to the left, all other terms to the right
-44n=35
n=35/-44
n=-35/44

See similar equations:

| 2x+6-1/3+1=6 | | 24=x*0.4 | | 4x+16=8x–20 | | Y=-5+(6x2) | | 7/3=2r-5/6r | | 1/9x=118 | | 24=-8+x | | 5y^2+4y-240=0 | | 25.92=x+.8x | | 2n^2+6n-340=0 | | 2(2n+5)=9(8n+6)+1 | | y=2(1/2)+9 | | -12+6=3x-6 | | -3x+5x=9+5x | | -5+6x=-x+9 | | -2-13.8=8x-(6x | | 60+2y=120 | | -4(x+5=-4x-20 | | 107+x=100 | | 4.43x10^-11=(1x10^-8)^x | | 4x-2x+9=8 | | 3x+2.3x+2+81=0 | | 3x-1=2×+7 | | -10y-9=11 | | 3x-47=115 | | 2(2x+4)=-5(3x-2) | | 7x-8x=-6 | | X.X-6x+5=0 | | -2(4s-1)-2=-2(8s+9)-2 | | x=10x100/20 | | 0=1/2x^2+(1/2) | | 0=1/2x^2+1/2 |

Equations solver categories